Unamuno y Verlaine: música y verso - Torre, Esteban (Rhythmica. Revista Española de Métrica Comparada, 2019)
Se analiza en este trabajo la oposición dialéctica existente entre el "Credo poético" de Miguel de Unamuno y el "Art poétique" de Paul Verlaine. Para Verlaine el verso es ante todo música, alada, ligera, sin peso. Para Unamuno, algo que no es música es la poesía, descarnada, pesada, seca. What is analyzed in this study is the discernible dialectical contrast between Miguel de Unamuno’s “Poetic Creed” and Paul Verlaine’s “Ars Poetica”. For Verlaine Poetry is primarily Music, wing-borne, airy, weightless. For Unamuno, that which is not Music is Poetry, stark, weighty, sere.